2019
DOI: 10.1140/epje/i2019-11855-2
|View full text |Cite
|
Sign up to set email alerts
|

Friction weakening by mechanical vibrations: A velocity-controlled process

Abstract: Frictional weakening by vibrations was first invoked in the 70's to explain unusual fault slips and earthquakes, low viscosity during the collapse of impact craters or the extraordinary mobility of sturzstroms, peculiar rock avalanches which travels large horizontal distances. This mechanism was further invoked to explain the remote triggering of earthquakes or abnormally large landslides or pyroclastic flows runout. Recent experimental and theoretical work pointed out the velocity of vibration as the key para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…This low apparent friction coefficient could be caused by a variety of factors, such as the lower basal friction coefficient than that in the experiments in Manzella (2008) and the low degree of fragmentation of blocks leading to less interaction between the fragments, which decrease the energy consumption of internal friction in our experiments. High‐frequency vibration of PMMA slabs may also lead to low friction to increase the bounce of fragments (Friedmann et al, 2006; Vidal et al, 2018; Wang et al, 2015). In addition, fragmentation may be one of the important reasons for the low apparent friction coefficient (Haug et al, 2016), which is demonstrated by the finding that the normalized total runout will increase with the degree of fragmentation (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This low apparent friction coefficient could be caused by a variety of factors, such as the lower basal friction coefficient than that in the experiments in Manzella (2008) and the low degree of fragmentation of blocks leading to less interaction between the fragments, which decrease the energy consumption of internal friction in our experiments. High‐frequency vibration of PMMA slabs may also lead to low friction to increase the bounce of fragments (Friedmann et al, 2006; Vidal et al, 2018; Wang et al, 2015). In addition, fragmentation may be one of the important reasons for the low apparent friction coefficient (Haug et al, 2016), which is demonstrated by the finding that the normalized total runout will increase with the degree of fragmentation (Figure 10).…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that the variation of energy consumption by internal deformation does not lead to inverse relationships of the friction coefficient. Mechanical vibration may also lead to spreading of fragments or friction weakening (Vidal et al, 2018). We did observe a slight vibration of the horizontal plane when analog blocks impacted and slid on the slab.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, let us mention that recent studies [30,52] have highlighted the role played by the velocity of the imposed mechanical vibrations on the frictional properties of sheared granular media. The friction reduction phenomenon occurring in a range of vibration frequencies in vertically shaken granular systems has been recently observed in experiments [36].…”
Section: A a Case Study: The Single Blockmentioning
confidence: 99%
“…These theoretical predictions are in very good agreement with numerical simulations and indicate that friction suppression is related to the reduction of effective interface contacts in the system due to the external vibrations. Finally, let us mention that recent studies [30,52] have highlighted the role played by the velocity of the imposed mechanical vibrations on the frictional properties of sheared granular media.…”
Section: Oscillations Inducing the Detachment Between Grains And The Confined Platesmentioning
confidence: 99%
“…In some cases, a relation K ∼ S α , with S ∼ (Af ) 2 , has been derived [26][27][28][29]. Experimental studies focused on the spe-cific role of the forcing mechanisms, such as vibration amplitude, frequency or velocity [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47]. In particular, an optimal frequency for energy transfer is found when the system is in a bouncing-bed state and A and f are varied keeping S fixed [30,31].…”
Section: Introductionmentioning
confidence: 99%